2009
DOI: 10.1111/j.1600-0560.2009.01270.x
|View full text |Cite
|
Sign up to set email alerts
|

A morphological study of granulomas induced by subcutaneous injection of leuprorelin acetate

Abstract: Leuprorelin acetate-induced granulomas in subcutaneous injection sites have been occasionally reported, but there have been no detailed morphological examinations. Histopathology of leuprorelin acetate-induced granulomas in six patients was studied, and one of them was evaluated by electron microscopy. Study using haematoxylin and eosin staining revealed that there were many intracytoplasmic vacuoles in the granulomas and degeneration of fat tissue. Ultrastructurally, electron-lucent spherical bodies (microcap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 12 publications
0
33
1
4
Order By: Relevance
“…Although very rare cases of foreign body reactions with leuprorelin have been reported, polylactic acid polymers are the main components involved . Moreover, the lipolytic action of LH‐RH in vitro is known and may interfere in the physiopathogenesis of this granulomatous reaction …”
Section: Discussionmentioning
confidence: 99%
“…Although very rare cases of foreign body reactions with leuprorelin have been reported, polylactic acid polymers are the main components involved . Moreover, the lipolytic action of LH‐RH in vitro is known and may interfere in the physiopathogenesis of this granulomatous reaction …”
Section: Discussionmentioning
confidence: 99%
“…Histopathological studies of these nodules have revealed subcutaneous injection site granulomas, with a central homogeneous collection . Granulomas have been associated with slow‐release polymers in other medications, such as leuprorelin . Degradable gels can induce a wide set of tissue responses, from localized granulomatous reactions to foreign body nodules and abscesses .…”
Section: Discussionmentioning
confidence: 99%
“…Although, a priori, it might be supposed that intramuscular compounds would be better absorbed than subcutaneous implants, there is no evidence supporting this [43]. A study with subcutaneous leuprorelin acetate [66] shows that the formation of granuloma is caused by both the foreign‐body reaction to the microcapsules and the lipolytic effect described for subcutaneous administration of the LHRHa [67]. Incidence would also be related to the dose administered [66].…”
Section: Indirect Evidence Obtained From Rctsmentioning
confidence: 99%